Biomodule - a combined structured and granulat media BAF - Williams, T. R.; Stephenson, Tom (Cranfield University, School of Water Sciences, 1999)
Biological aerated filters operate as fixed film systems in which micro-organisms grow on a submerged fixed structured or granular inert support media within an aerated reactor (Stephenson et al., 1993). Periodic backwashing of the filter is required as the media bed gradually clogs due to the growth of biomass and retention of solids. The advantage of the BAF process is the small footprint it occupies relative to comparable processes such as activated sludge and trickling filters. The small footprint is due to the fact that the fixed film of biomass on the support material (media) leads to a high concentration of active bacteria per unit volume of the media and thereby to relatively small reactors. Another advantage is the retention of suspended solids that eliminate the need for final sedimentation tanks (Hagedorn et al., 1994). For the same degree of treatment, biofilters require approximately three times less aeration volume than activated sludge units, and twenty times less than trickling filters (Smith et al., 1992). In summary BAF systems are used for providing a treatment method for reducing the amount of organic carbonaceous material (BOD/COD), suspended solids and ammonia in wastewater.